Mental health among elite youth athletes: A narrative overview to advance research and practice - Walton, C. C.; Purcell, R.; Henderson, J. L.; Kim, J.; Kerr, G.; Frost, J.; Gwyther, K.; Pilkington, V.; Rice, S.; Tamminen, K. A. (Sports Health: A Multidisciplinary Approach, 2024)
Context: Participation in sports during youth is typically beneficial for mental health. However, it is unclear whether elite sport contexts contribute to greater risk of psychological distress or disorder. The aims of this paper are to highlight conceptual issues that require resolution in future research and practice, and to examine the key factors that may contribute to the mental health of elite youth athletes (EYAs).